Treatment of Palm Oil Mill Effluent (POME) using Membrane Anaerobic System (MAS) - Mohamed, Hybat Salih; Nour, A. H.; Zaki, Yasmeen Hafiz; Zulkifly, Jemaat; Azhari, H. Nour (IOP Publishing, 2019)
The directly discharged of Palm Oil Mill Effluent (POME) into the river causes environmental hazards due to the biochemical oxygen demand (BOD) and high Chemical Oxygen Demand (COD). The main issue of the traditional methods for POME treatment is that are not suitable for high suspended solid wastewaters and their gas production is less efficient at a high treatment volume. Therefore, in this study Membrane Anaerobic System (MAS) was used as alternative effective method for treating POME. The result obtained from the six steady states with concentration ranging from 11,048 to 15,700 mg/L mg/L for the MLSS, while the MLVSS recorded a concentration range between 10,540 and 17,600 mg/L. Moreover, the COD removal efficiency and HRT recorded from 94 to 97% and 150 to 10 days, respectively. Also, the coefficient of microorganism yield, decay rate, and the produced methane gas were obtained as 0.52g VSS/g COD, 0.31 day-1 and 0.182 to 0.564 l/g, respectively. Kinetic equations from Monod, Contois, and Chen, & Hashimoto were employed to describe the kinetics of POME treatment at organic loading rates ranging from 0.5 to 13 kg COD/m3/day. POME were characterized using Transform Infrared (FTIR) spectroscopy, in the regions of 900 to 1740 and 2800 to 3400 cm-1. Scanning Electron Microscope (SEM), the obtained result confirmed the potential of Membrane Anaerobic System (MAS) for the efficient treatment of POME effluent.